Dimensions of Emancipation: Rethinking Subjectivity, Domination and Temporality in Feminist Theory. (1st May 2016) - Lettow, Susanne
Abstract : "Emancipation" is one of the most opaque words in political language and political theory. It refers to the hope of overcoming all forms of domination, yet is articulated with the highly ambivalent notions of reason, progress, equality and liberty, and with the unfulfilled utopias that accompany them. In light of the different and contested uses that have been made of the concept of emancipation within and beyond contemporary feminist theory, I argue that a close examination of the concept and of the unresolved political and theoretical questions it articulates is a timely endeavour. With reference to Reinhard Koselleck's conceptual history of emancipation, in which he highlights three de- velopments that helped to shape the modern concept of emancipation – first, the turn towards a reflexive understanding of emancipation as self-emancipation; second, the politicisation of the concept; and third, its temporalisation – I examine the ways in which subjectivity, domination and temporality have been articulated in contemporary feminist theory.